The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s12119-017-9461-7
|View full text |Cite
|
Sign up to set email alerts
|

BDSM, Interaction Rituals and Open Bodies

Abstract: In this article, based on ethnographic fieldwork in Bondage and Discipline, Dominance and Submission, Sadism and Masochism (BDSM) communities in Sweden, I explore the ritual aspects of BDSM. Drawing on Douglas and Collins' theories of interaction rituals, I analyse the creation of emotional energy during humiliation practice through connection and intimacy between the participants. The article examines how the ritual aspect of BDSM sessions can be understood as an enabler of expressions and emotional energy. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…51 As with dance music, the collective intimacy and vulnerability at the heart of the BDSM practice forms an emotional narrative from individual "desire, anticipation and excitement" to "shared group-dynamic feelings… of joining, love, affection [and] fellowship". 52 The common focus and a supportive group dynamic of both scenarios instils a deep and long-lasting sense of belonging in participants, which facilitates community-building and motivates them to repeat the ritual.…”
Section: An Alternative Readingmentioning
confidence: 99%
“…51 As with dance music, the collective intimacy and vulnerability at the heart of the BDSM practice forms an emotional narrative from individual "desire, anticipation and excitement" to "shared group-dynamic feelings… of joining, love, affection [and] fellowship". 52 The common focus and a supportive group dynamic of both scenarios instils a deep and long-lasting sense of belonging in participants, which facilitates community-building and motivates them to repeat the ritual.…”
Section: An Alternative Readingmentioning
confidence: 99%
“…30–39; Odent, 2001). Carlström (2018) noted that in Western society, the widely accepted view is that the functional body ought to be clean and hygienic; contact with body fluids is, in many situations, surrounded by taboos. However, body fluids are integral to natural birth, a process steeped in blood, urine, and feces.…”
Section: Birthing Consciousness As a Case Of Transient Hypofrontalitymentioning
confidence: 99%
“…Additionally, BDSM experience is shaped by one's culture, social positioning, and specific identity attributes, including gender (Simula, 2019;Simula & Sumerau, 2018). Many individuals who engage in diverse erotic behaviors are psychologically well-adjusted individuals and may be members of alternative sexuality communities (Carlström, 2018). A recent review of the literature found that BDSM may function as legitimate leisure experience-typically associated with a sense of freedom, sense of adventure, decreased stress, and positive emotions-for large numbers of participants, while also being a particular sexual identity for some (Sprott & Williams, 2019).…”
Section: Diverse Sexual Interests and Practicesmentioning
confidence: 99%